Flight - Zemeckis, Robert, 1952-; Gatins, John.; Parkes, Walter F.; Washington, Denzel, 1954-; Cheadle, Don.; Reilly, Kelly; Goodman, John, 1952-; Greenwood, Bruce, 1956-; Leo, Melissa; Paramount Pictures Corporation; ImageMovers (Firm); Parkes/MacDonald Productions (Hollywood, CA : Paramount Pictures, 2013)
Airline pilot, Whip, miraculously crash lands his plane after a mid-air catastrophe, saving nearly every soul on board. After the crash, Whip is hailed as a hero, but as more is learned, more questions than answers arise as to who or what was really at fault and what really happened on the plane.
Originally released as a motion picture in 2012.
Director of photography, Don Burgess ; editor, Jeremiah O'Driscoll ; music, Alan Silvestri.
Denzel Washington, Don Cheadle, Kelly Reilly, John Goodman, Bruce Greenwood, Melissa Leo.
MPAA rating: R; for drug and alcohol abuse, language, sexuality/nudity and an intense action sequence.
DVD; widescreen (2.35:1) presentation; audio description; Dolby Digital 5.1; NTSC, region 1.
English, French or Spanish dialogue; Spanish, Portuguese, French or English subtitles; closed-captioned.
Keywords: Air pilots -- Drama; Aircraft accidents -- Investigation -- Drama; Feature films; Thrillers (Motion pictures); Video recordings for the hearing impaired; Video recordings for people with visual disabilities